Prevention of Contrast Induced Nephropathy in Patients Undergoing Coronary Angioplasty by Pretreatment with High Dose Atorvastatin (Journal of Medical & Health Sciences Review, 2025)
One potential side effect of coronary angioplasty for the development of acute kidney injury (AKI) is contrast-induced nephropathy (CIN). New data show that atorvastatin, decreases the risk of CIN by its anti-inflammatory and endothelium-stabilizing properties. This paper sought to assess high dose atorvastatin pretreatment in the prevention of CIN in patients who are candidates for coronary angioplasty. This prospective descriptive comparative study was carried out in the department of Cardiology,  PAEC Hospital,  Islamabad, from 1st August 2024 till 31st December 2024. A total of 214 patients, were equally assigned to two groups: the Atorvastatin Group, comprised of 107 participants and the Control Group comprised of 107 participants. In atorvastatin group, patients took 80mg of orally before 24 hours of angioplasty procedure was done. Routine preoperative IV saline 1 mL/kg/h was given 12 h before and after the procedure. No statin pretreatment was given to patients in control group but they were offered the same level of hydration. Mean age in study group versus control group was (63.2 ± 10.4 years vs. 62.8 ± 11.2, p = 0.685) respectively. The majority of patients (67.3% in the atorvastatin group and 65.4% in the control group) were male. The mean contrast volume employed during the procedure was 180.2 ± 25.0 mL in the atorvastatin group and 185.1 ± 30.2 mL in the control group; p = 0.34. High dose atorvastatin administration before coronary angioplasty decreases the incidence of CIN, suggesting that this is a secure and efficient way to maintain renal function.